The impact of FDI inflows on R&D activities in developing countries: a panel data analysis - Mahamad Zakaria, Muhammad Farhan; Wan Ngah, Wan Azman Saini; Law, Siong Hook (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
This study investigates the impact of FDI inflows on R&D activities in 48 developing countries for the 1996-2013 periods. The results based on the system Generalized Method of Moment (GMM) estimator show that FDI inflows tend to discourage R&D activity in developing countries. Additionally, there is evidence that R&D activity benefits from import and stronger legal protection.